IMMEDIATE RESULTS OF PERCUTANEOUS TRANS-MITRAL COMMISSOROTOMY IN JUVENILE MITRAL STENOSIS - Ahsan Beg (Army Medical College Rawalpindi, 2020)
Objectives: Immediate result of PTMC in juvenile (5-12 years) rheumatic mitral stenosis.